Comparative Study of Fe‐Doped ZnO Nanowire Bundle and Their Thin Film for NO2 and CH4 Gas Sensing. Issue 1 (November 2015) - Vyas, Rishi; Sharma, Sarla; Khan, Shabana; Divakar, R.; Sachdev, K.; Sharma, S. K.
Summary: The free standing Fe‐doped ZnO nanowire bundle is synthesized by employing a typical vapor phase transport method in single step from Fe+Zn powder in O2 +Ar flow. Fe‐doped ZnO nanowires are characterized by Transmission Electron Microscopy (TEM) and Energy Dispersive Spectroscopy (EDS) suggesting formation of hexagonal wurtzite phase of ZnO with 7 at% Fe in ZnO with typical nanowire diameter in the range of 20 nm–70 nm. These nanowire bundles are ultrasonicated and processed into thin film using spin coating technique. Both of the Fe‐ doped ZnO nanowire bundle and thin films are tested for their NO2 and CH4 (20–100 ppm) sensing properties. The thin film exhibited higher operating temperature (300°C) and response time (45 sec) as compared to nanowire bundle (150°C and 15 sec).